Biomechanical assessment of healthy and keratoconic corneas (with/without crosslinking) using dynamic ultrahigh-speed Scheimpflug technology and the relevance of the parameter (A1L-A2L) - Fuchsluger, Thomas; Brettl, Susanne; Geerling, Gerd; Kaisers, Wolfgang; Zeitz, Philipp Franko (British Journal of Ophthalmology, 2019)
Aims To examine corneal biomechanics in healthy and keratoconic eyes, with or without crosslinking obtained by ultrahigh-speed Scheimpflug measurements (Corvis ST).
CRIS-Team WoS Importer:2019-07-02